Fabrication of capacitive pressure sensor with extraordinary sensitivity and wide sensing range using PAM/BIS/GO nanocomposite hydrogel and conductive fabric. (June 2021) - Wu, Guanzheng; Panahi-Sarmad, Mahyar; Xiao, Xueliang; Ding, Fuchuan; Dong, Ke; Hou, Xiuliang
Abstract: Herein, a flexible and robust hydrogel, polyacrylamide hydrogel containing graphene oxide and N, N-isopropyl di-acrylamide, was developed through a novel in-situ synthesis procedure. A high-sensitive capacitive pressure sensor was then fabricated through an assembly of the hydrogel wrapped by an insulated ultra-thin polyethylene film as the primary dielectric, and two soft-plated woven fabrics as conductive layers. The nanocomposite (NC) hydrogel displayed superior strength and resilience that the breaking strength and elongation at break are close to 45 kPa and 2110%, and a 50% cyclic compressive strain for 50 times along with a compressive strength of 84.17 kPa was exhibited, implying NC-hydrogel was ideal. The sensitivity of the as-made capacitive pressure sensor reached incredibly up to 2.6; the sensing range was available from 0 ~ 80%. Consequently, this conductive pressure sensor is profoundly high-potential for capturing some slight limbs' movements and strain in response to even the slightest amounts of pressure.